Trajetórias de intelectuais na educação : o trabalho do pensamento e seus impactos nas ciências sociais (1964-2020) - Barros, Tainá Martins de (Universidade do Vale do Rio dos Sinos, 2024)
The present research has as its object of investigation the academic career of four professors, namely: Ivo Follmann, Clarissa Eckert, Lorena Holzmann and Ruben Oliven. The present study aims to answer the following problem: how did the education, teaching, research and work of these social scientist teachers take place between the years 1964-2020? In order to answer this question, this research has the general objective of this research is to produce, based on memory narratives, the trajectories of teachers in the field of Social Sciences, focusing on their intellectual paths between 1964-2020. The specific objectives are: to understand the path of these teachers, based on the elements that compose their education, performance and production itineraries; identify and reflect on the contributions of the four chosen teachers to the field of Social Sciences; establish possible connections or not between the teachers' itineraries, examining the differences, distinctive marks, similarities and sociability networks also produced. The theoretical methodological framework used in the research belongs to the History of Education and is anchored in Cultural History, based on a micro-historical approach. To understand the concept of Trajectory, the research mobilizes Bourdieu (2006) and, to discuss intellectuals, uses Jean-Fraçois Sirinelli (1994; 1996). The methodology used is Oral History, where memory is considered a document. For this methodology, I based myself on Alessandro Portelli (2016) and Ecléia Bosi (1987). To make considerations about memory, I turn to Paul Ricouer (2007; 2007b), Michel Pollak (1989) and some reflections by Luciane S. S. Grazziotin (2016). Reconstructing their trajectories, it was possible to see that Ivo Follmann actively contributed to the Sociology of Socio-Environmental Movements; Clarissa Eckert contributed to studies related to Higher Education in Brazil; Lorena Holzmann enriched the debate on the Sociology of Work; and Ruben Oliven was important for the transformations of Anthropology in Brazil.
Keywords: Trajetória; Intelectuais; História da Educação; Trajectory; Intellectuals; History of Education; ACCNPQ::Ciências Humanas::Educação